1976
DOI: 10.1159/000122628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ventromedial and Dorsomedial Hypothalamic Lesions on Circadian Corticosterone Rhythms

Abstract: Weanling rats received bilateral electrolytic lesions in the dorsomedial (DMH) or ventromedial (VMH) hypothalamic areas destroying primarily the dorsomedial (DMN) or ventromedial (VMN) hypothalamic nuclei. Sham-operated rats served as controls. Lesions in the VMN and DMN, both of which have previously been shown to disrupt normal diurnal feeding rhythms, were also observed to disrupt normal plasma corticosterone rhythms in the present study. The a.m. values of plasma corticosterone in the DMN-lesioned rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…Food intake is decreased at night; however, body weight, insulin, leptin, and fat depot weights do not change. These results agree well with those of Bellinger and Bernardis (14,30,31), who show that lesions of the DMN in weanling rats result in small adults that eat less but strictly in proportion to body weight, and thus have normal body composition. Our other studies (submitted) show that rats with DMN disruption are more sensitive than sham-disrupted rats to the effects of intracerebroventricularly administered leptin, suggesting that the DMN normally abrogate, to some extent, the dominant inhibitory effects of leptin, and possibly other signals of energy stores, on food intake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Food intake is decreased at night; however, body weight, insulin, leptin, and fat depot weights do not change. These results agree well with those of Bellinger and Bernardis (14,30,31), who show that lesions of the DMN in weanling rats result in small adults that eat less but strictly in proportion to body weight, and thus have normal body composition. Our other studies (submitted) show that rats with DMN disruption are more sensitive than sham-disrupted rats to the effects of intracerebroventricularly administered leptin, suggesting that the DMN normally abrogate, to some extent, the dominant inhibitory effects of leptin, and possibly other signals of energy stores, on food intake.…”
Section: Discussionsupporting
confidence: 92%
“…Refs. 11,13,14).Because all four of the medial hypothalamic cell groups have been implicated in the regulation of energy balance (15), reported to contain leptin receptors (16,17), and strongly interconnected (18 -22), it is important to distinguish among them, if possible, to learn more about functions in each nucleus.We used small injections of colchicine (23) to inhibit function in each of four medial hypothalamic cell groups so that we could determine the specific effects of inhibition in a given cell group on food intake, hormones, and fat stores. Previous studies using colchicine as a reversible neurotoxin have shown acute responses that are identical to those of irreversible excitotoxin lesions (23,24).…”
mentioning
confidence: 99%
“…Lesions of the VMH, but not the suprachiasmatic nucleus, abolish this change in circadian corticosterone levels in food restricted rats (50,51). Additionally, lesions or inhibition of the VMH alter diurnal corticosterone rhythms (54)(55)(56). These findings suggest that the VMH may be critical in linking nutritional status into circadian neuroendocrine responses.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, VMH lesions interfere with the diurnal rhythms of plasma corticosterone levels and food intake (Balagura and Devenport, 1970;Bellinger et al, 1976;Bernardis, 1973). There is also general agreement that the VMH plays important roles in the regulation of feeding (Brooks et al, 1946;Minano and Myers, 1991;Perkins et al, 1981;Shimizu et al, 1987), defensive (Fuchs et al, 1985a;, and feminine copulatory behaviors and the modulation of autonomic responses associated with these behaviors.…”
Section: From a Neuroendocrine Aspect It Is Interesting To Note Thatmentioning
confidence: 99%